Sr/Smco-doped hydroxyapatites: experimental characterization and theoretical research - Hssain, Ala Hamd; Bulut, Niyazi; Ates, Tankut; Koytepe, Suleyman; Kurucay, Ali; Kebiroglu, Hanifi; Kaygili, Omer (Springer, 2022)
This paper goes into extensive detail about the theoretical and experimental characterization of Sr doped hydroxyapatite (HAp) samples that have been doped with Sm in various amounts. To accomplish this, five HAps containing a constant 0.133at.% of Sr were additionally doped with Sm at varied amounts and synthesized by a method of wet chemical. In addition, the density functional theory (DFT) was used to model all of these samples. According to theoretical results, the bandgap energy declined continuously from 4.6297 to 4.4034eV. The linear absorption coefficient increased with increasing amounts of Sm in all samples, while this parameter decreased with increasing photon energy. There was a reduction in both the lattice parameter a and the volume of the unit cell, but there was also an increase in the lattice parameter c and theoretical density. Accordingly, the experiment's results were as follows:HAp phase (above 98% for all of the samples) and beta-tricalcium phosphate beta - TCP were both confirmed as the major phase and minor phase, respectively, by X-ray diffraction (XRD), FT-Raman spectroscopy and the Fourier transform infrared (FTIR) measurements. The addition of Sm increased in the beta - TCP phase from 0.62 to 0.86%. Same as theoretical results, it was also found that density was increasing and the volume of the unit cell decreased. An increase in anisotropic energy density and a decrease in crystallinity were discovered. The values are calculated based on the molar ratio, which was discovered to be close to those for stoichiometric HAp in all samples (1.67). Based on the results of the thermal study, all samples were confirmed to be thermally stable. Sm content was discovered to have an effect on cell viability.
Keywords: Hydroxyapatite; DFT calculations; Band structure